La France et le Brésil de l’Oyapock, quels enjeux bilatéraux entre développement et durabilité ? - Raimundo Nonato Junior (Confins)
This article is based on a geographical comparison of French and Brazilian territorial policies on the frontier between French Guiana and the Brazilian state of Amapá. In particular, our paper focuses on the conception of developments and sustainability around the Oyapock boarder. These peripheral regions are severely dependent from their respective central states. Local economic exchange however, promises to offer a strategy of reconciliation between Europe and Brazil. In that context, concepts of “development” and “sustainability” are important in different scales. Then, a comparison between local and national scales became a way to ask about the differences and dialogues in Oyapock border region.